Intracranial vascular calcification with extensive white matter changes in an autopsy case of pseudopseudohypoparathyroidism. Issue 1 (14th November 2018) - Iwase, Tamaki; Yoshida, Mari; Hashizume, Yoshio; Yazawa, Ikuru; Takahashi, Seishiro; Ando, Takashi; Ikeda, Toshimasa; Nokura, Kazuya
Abstract : We herein report an autopsy case of a 69‐year‐old man with pseudopseudohypoparathyroidism. The patient suffered from mental retardation and spastic tetraparesis and had all the features of Albright's hereditary osteodystrophy with a normal response to parathyroid hormone in the Ellsworth–Howard test. Computed tomography demonstrated symmetrical massive brain calcification involving the bilateral basal ganglia, thalami, dentate nuclei and cerebral gray/white matter junctions, which was consistent with Fahr's syndrome. Magnetic resonance imaging revealed extensive white matter changes sparing the corpus callosum. Severe ossification of the posterior longitudinal ligament of the cervical spine was also demonstrated. A neuropathological examination revealed massive intracranial calcification within the walls of the blood vessels and capillaries with numerous calcium deposits. The calcium deposits aligned along the capillaries, and deposits in the vessel wall at the initial stage were confined to the border between the tunica media and adventitia. The vascular calcification in the basal ganglia continuously spread over the surrounding white matter into the cortex. The area of vascular calcification in the white matter was very well correlated with the area of the attenuated myelin staining. Axonal loss, myelin sheath loss and gliosis were observed in the white matter with severe vascular calcification. We should recognize the continuous area of vascular calcification and its correlation with extensive white matter changes as possible causes of neuropsychiatric symptoms in pseudopseudohypoparathyroidism with Fahr's syndrome.